Enhanced Method OF Through-hole Copper Plating - Otáhal, Alexandr; Crha, Adam; Šimek, Václav (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
This paper is dealing with an introduction of novel approach conceived towards the optimization of widespread through-hole copper plating process. Main objective in this context is to achieve significantly increased process reliability and overall fabrication yield also for the smallscale production runs or prototyping purposes of printed circuit boards. Essential aspect of the procedure outlined in this paper is inherently connected with the activation of printed circuit board surface, which serves as the basis for the subsequent step that involves the conformal copper plating of holes drilled through the substrate compound. An innovative part of the whole process can be recognized in activation of drilled holes surface by means of employing combination of vacuum (low pressure environment) and ultrasound within the dedicated setup. The application of the suggested procedure helps to considerably reduce the failure ratio (i.e. the presence of holes with faulty surface plating) even in case of drilled holes at considerably small dimensions and, as a direct consequence, improves the overall process reliability.
Keywords: Through-hole technology; copper plating; PCB